Determining the nutrient content, energy, and in vitro true digestibility of some grass forage plants - GÜRSOY, Esra; KAYA, Adem; GÜL, Mehmet (Emirates Journal of Food and Agriculture, 2021)
The purpose of this study was to compare the chemical composition, metabolizable energy, net energy lactation, total digestible nutrient, in vitro digestion parameters, and relative feed quality of some grass forage plants growing naturally in the meadows and pastures of Erzurum province in Turkey. Orchardgrass (Dactylis glomerata), Variegated brome (Bromus variegatus), and Intermediate wheatgrass (Agropyron intermedium) were used as the research material. In this study, the metabolizable energy (ME) and net energy lactation (NEL) contents of the green grass crops forage plants were determined by in vitro gas production method, and their digestibility parameters and relative feed quality (RFQ) by the neutral detergent fiber (NDF) procedure using an Ankom Daisy incubator. As a result of the study, the differences between the forage plants were found to be statistically significant in terms of chemical composition, metabolizable energy, net energy lactation, true organic matter digestibility (TOMD) and RFQ (P<0.05). While the green intermediate wheatgrass was found to have the highest crude protein (CP) (19.56%), crude fat (CF) (3.06%), dry matter (DM) (9.14%), ME (8.82%), NEL (5.42%), and TOMD (97.75%); the green variegated brome was found to have the highest RFQ (149.79). The green orchardgrass was found to have the highest contents of neutral detergent fiber (NDF), acid detergent fiber (ADF), and acid detergent lignin (ADL) with 66.23%, 34.14, and 8.52%, respectively. In conclusion, the green grass forage plants examined in this study can be used to eliminate the quality roughage deficit.